Frequency and Determinants of Maternal Anaemia in Early Postpartum Period - Syeda Rabia; Nadia Jalil; Sarah Feroze; Mehreen Iqbal (KARACHI MEDICAL AND DENTAL COLLEGE, 2018)
Objective: To determine the frequency and risk factors of maternal anaemia after delivery. Methods: A cross-sectional study was carried out in two private tertiary care hospitals of Karachi over a period of six  month  from April  to  October  2017. A sample  of  300  postpartum  women  was  recruited in the study by convenient sampling. Inclusions criteria were women more than 24 hours or up to one week following delivery of babies of  more than 28 weeks of gestation and all booked cases of hospitals that consented to take part in re-  search study. Exclusion criteria were  women  who  had  no  antenatal  visits  and  haemoglobin  estima-  tion in third trimester of pregnancy. Data was collected using predesigned  questionnaire  after  taking  informed  consent.  Haemoglobin  lev- els were noted in early pregnancy, third trimester and postpartum period. Results: The study group comprises of 135 (47.9%) women with postpartum anaemia, whereas 147 (52.1%) women had normal level of haemoglobin. A total of 72 (25.5%) women had a rise in haemo- globin,192  (62%)  women  had  low  and  18  (6.4%)  women  had  unchanged  postpartum  haemoglobin  as compared to the third trimester haemoglobin level. The mean age of the study group was 27.59 ± 4.221. Inadequate iron intake was noted in 66 (48.9%) women in the anaemic group, whereas it was found in 51 (34.7%) women in the non-anaemic group (p-value=0.000, OR=0.083). Anaemia was diagnosed during pregnancy in 105  (77.8%)  women  in  anaemic group, whereas 33 (22.4%) women had anaemia during  pregnancy  in  non-anaemic  post-  partum group (p-value=0.000, OR=0.083). Caesarean  section  was  performed  in  84  (62.3%)  women  with postpartum anaemia (p-value=0.010, OR=0.537). A total of 27 (20%) women  with  postpartum  anaemia had episiotomy during normal vaginal or instrumental deliveries (p-value=0.042, OR=1.765). Conclusion: Frequency of early postpartum anaemia is  high.  Anaemia  during  pregnancy,  inadequate iron intake, vaginal delivery with episiotomy and caesarean section were significant risk factors.